Custom cost of commodity: problem aspects and ways of their decision - Lyuba, Oksana (Herald of Economics, 2022)
Introduction. One of basic constituents of custom business there is a custom cost. Changes that take place during the last years from the moment of receipt by our state of independence, render substantial influence on forming of institute of custom cost in Ukraine. For today, one of major factors that have negative influence on the economy of Ukraine there is imperfection of methodology of determination of custom cost of commodities at their declaration. Custom payments form considerable profitable part of budget of the state, that is why authenticity of statement of custom cost is an extraordinarily important question, both for the subjects of foreign economic activity, that declare commodities, and for public authorities that carry out control after the rightness of her determination. Often between the adopted parties there are conflict situations the decision of that needs government control in the field of a custom cost and her accordance to the norms of international law.A research aim is research of problems that arise up at the choice of method and numerical value of custom cost and development of ways of their decision.Research methods. In the article the scientific methods of research are applied: synthesis, analysis, and also analysis of the systems and method of logical generalization. Results. Prelude of Ukraine of World organization of trade, and also the first steps on the way of integration to European Union, in a considerable measure need the improvement of the custom-tariff adjusting of foreign economic activity. One of key constituents there is a custom cost of commodities, that serves as a base at the extra charge of custom payments and participates in forming of profitable part of the state budget. The custom cost of commodity serves as an object for discussions and manipulations at declaration of commodities, that gives possibility to do a result about expedience of search of ways for reformation of institute of custom cost, and also to give suggestions in relation to the removal of abuses at determination of her method and numerical value. Research results testify that for the removal of problem questions that take place at determination of numerical value and method of custom cost, expediently: to bring to conformity position of Custom Code of Ukraine under right international customs legislation, in part, that touch the custom cost of commodities; to provide a direct order at application of methods of custom cost under right Custom Code of Ukraine; to oblige parties of process of declaration of commodities to the necessity of realization of writing consultations in relation to electing of method of determination of custom cost; to define the clear list of additional documents that will be given by a broker or person authorized by him for confirmation of the declared custom cost; to oblige custom authority, at awarding judgement about adjustment of custom cost, to give the exhaustive list of grounds according to that every previous method of determination of custom cost can not be applied; to reduce the terms for the grant of additional documents for confirmation of the declared custom cost; to decrease the terms of completion of custom registration of commodity and awarding judgement about adjustment of the custom cost declared a broker; to set the checking system above a price on raw material at her apartment in the mode of processing on custom territory of Ukraine.The prospects of further researches consist in the search of possible ways of improvement of institute of custom cost due to bringing to conformity of customs legislation of Ukraine in accordance with international custom norms and positions.